The links between parental smoking and childhood obesity: data of the longitudinal study of Australian children - Preety Srivastava; Trong-Anh Trinh; Karen T. Hallam; Leila Karimi; Bruce Hollingsworth (BMC, 2024)
Abstract Childhood obesity is one of the most concerning public health issues globally and its implications on mortality and morbidity in adulthood are increasingly important. This study uses a unique dataset of Australian children aged 4-16 to examine the impact of parental smoking on childhood obesity. It confirms a significant link between parental smoking (stronger for mothers) and higher obesity risk in children, regardless of income, age, family size, or birth order. Importantly, we explore whether heightened preference for unhealthy foods can mediate the effect of parental smoking. Our findings suggest that increased consumption of unhealthy foods among children can be associated with parental smoking.